An Examination of the Effects of Frugal (simple) Innovation Environmental and Economic Performance of SMEs - Dr Javed Meraj; Jamal Shah; Adul Qadeer; Salman Khan (Research Journal of Psychology, 2025)
In this research, simple innovation and small and medium-sized enterprises (SME)s’ environmental and financial performance are under analysis. Simple innovation, characterized by resource-efficient and cost-effective approaches, is examined for its role in fostering sustainable solutions and enhancing business outcomes. The research highlights how SMEs adopting simple innovation minimize ecological footprints through optimized resource use and waste reduction while achieving cost savings and increased market competitiveness. The findings reveal a dual effect: simple innovation significantly benefits environmental performance but presents complexities in its financial outcomes, moderated by organizational proactivity. The results underline the strategic importance of simple innovation for addressing global challenges such as resource scarcity and economic inequality, offering a pathway for sustainable growth in both emerging and developed markets. This study provides actionable insights for SMEs and policymakers, emphasizing the need to integrate simple innovation into business strategies. Future research should explore sector-specific applications and long-term implications to maximize its potential.